PENGARUH KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, PROFITABILITAS, GROWTH OPPORTUNITY, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Claresta Dara Hermawan Putri, 13.05.52.0182; Aini, Nur (Students Journal of Accounting and Banking, 2018)
The purpose of this tudy is to examine the influence of debt policy, dividend policy, profitability, growth opportunity, and firm size on the value of companies in manufacturing companies listed on the Indonesia Stock Exchange.The dependent variable in this research is company value. And the independent variables are debt policy, dividend policy, profitability, growth opportunity, and company size. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2013-2015. The sample selection is done by purposive sampling method. The data is processed as many as 98 companies. The technique of data testing is by using multiple linear regression analysis. The result of analysis is known that the variable of debt policy has a negative effect on company value, while profitability and firm size have positive influence to company value, then dividend policy and growth opportunity have no effect to company value.Keywords : Debt Plicy, Dividend Policy, Profitability, Growth Opportunity, Company Size, Corporate Value.